Alumina Extraction from Red Mud by Magnetic Separation - Suprapto Suprapto; Zahrotul Istiqomah; Eko Santoso; Ahmad Anwarud Dawam; Didik Prasetyoko (Universitas Gadjah Mada, 2018)
Alumina extraction from red mud has been investigated by magnetic separation with three-step treatment. First, the addition of red mud with Na2CO3 (12 wt%) and heated at 110 °C for 4 h. The second step was carbon reduction using coal with mass ratio of (red mud+Na2CO3) : coal was 1:3 then roasted at temperature of 850, 950, and 1050 °C for 1, 2, and 3 h. The third step was magnetic separation. The magnetic separation was carried out in order to remove magnetite produced during roasting process. Magnetic and non-magnetic phases obtained were characterized by XRD and SEM-EDX techniques. The non-magnetic phase obtained was leached using HCl 6 M, and then aluminum content was determined by Inductively Coupled Plasma (ICP). The result revealed that the highest aluminum oxide extracted from the red mud was 20.66 wt% obtained by roasting at temperature of 1050 °C for 2 h.